2009
DOI: 10.1007/s12253-009-9160-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Prognostic Markers in Intracranial Ependymomas: Systematic Review and Meta-Analysis

Abstract: Distinction between grade II ependymomas and anaplastic ependymomas based on histopathological examination solely is problematic and, therefore, the management of intracranial ependymomas remains controversial. The aim of this study was to conduct a systematic review (SR) and meta-analysis (MA) of data published on immunohistochemical prognostic markers (IPM) in intracranial ependymomas (IE), and to establish an evidence-based perspective on their clinical value. Following the extensive search based on a stric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
2
16
0
2
Order By: Relevance
“…Based on the evidence, MIB-1 labeling index correlates with the grade of malignancy in ependymal tumors. 19,25 We also found that MIB-1 expression has a reverse correlation with H3K9Ac expression in tumors such that tumors with higher MIB-1 expression had lower H3K9Ac levels and vice versa. Concerning ependymal tumors, to the best of our knowledge, there are no previous reports on histone acetylation levels either by the gene candidate approach on specific promoter regions or by analysis of global histone acetylation changes at the cell level.…”
Section: Discussionmentioning
confidence: 64%
“…Based on the evidence, MIB-1 labeling index correlates with the grade of malignancy in ependymal tumors. 19,25 We also found that MIB-1 expression has a reverse correlation with H3K9Ac expression in tumors such that tumors with higher MIB-1 expression had lower H3K9Ac levels and vice versa. Concerning ependymal tumors, to the best of our knowledge, there are no previous reports on histone acetylation levels either by the gene candidate approach on specific promoter regions or by analysis of global histone acetylation changes at the cell level.…”
Section: Discussionmentioning
confidence: 64%
“…Kaplan-Meier methods were used to estimate median, 1, 2, 3, 5 and 10 year OS and PFS for all patients overall, and within strata defined by Tenascin C, histologic grade and CA IX status (B5/ [5). The log-rank test was used to compare survival distributions between patient subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence points to loco-specific biologic differences mediating growth [1, 3,4]. For example, site-specific findings such as mitotic activity, vascular proliferation and necrosis are robust markers of prognosis in posterior fossa ependymomas, but not in spinal cord ependymomas [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Há, também, estudos com marcadores imuno-histoquímicos, porém sem resultados definitivos (Korshunov, Golanov et al 2002;Zamecnik, Snuderl et al 2003;Kuncova, Janda et al 2009;Zawrocki, Izycka-Swieszewska et al 2011). …”
Section: Grau Histológicounclassified
“…A busca por biomarcadores para melhor predizer a evolução clínica dos pacientes com ependimoma tem sido realizada por muitos autores (Gilbertson, Bentley et al 2002;Korshunov, Golanov et al 2002;Preusser, Wolfsberger et al 2005;Mendrzyk, Korshunov et al 2006;Ridley, Rahman et al 2008;Tabori, Wong et al 2008;Kuncova, Janda et al 2009;Korshunov, Witt et al 2010;Milde, Hielscher et al 2012;Modena, Buttarelli et al 2012;Moreno, Popov et al 2013;Mack, Witt et al 2014). Apesar dos ependimomas serem considerados como uma única doença devido às mesmas características histológicas, a maioria dos estudos mostra um perfil de expressão gênica diferente dependendo da localização do tumor e da idade do paciente ao diagnóstico (Hirose, Aldape et al 2001;Dyer, Prebble et al 2002;Taylor, Poppleton et al 2005;Modena, Lualdi et al 2006;Kilday, Rahman et al 2009;Palm, Figarella-Branger et al 2009;Andreiuolo, Puget et al 2010;Johnson, Wright et al 2010;Witt, Mack et al 2011;Nagasawa, Trang et al 2013).…”
Section: Spearman (Figura 15)unclassified